Correlation of Surrogate Markers of Insulin Resistance with Fasting Insulin in Type 2 Diabetes Mellitus Patients: A Study of Malwa Population in Punjab, India - Kaur, Navneet; Gitanjali; Garg, Ravinder; Tapasvi, Chaitanya; Chawla, Sonia; Kaur, Navdeep (Journal of Laboratory Physicians, 2021)
Context Insulin resistance (IR) and abnormal insulin secretion play a key role for the development of type 2 diabetes mellitus (DM).Aims We investigated the surrogate markers of IR, i.e., Homeostasis Model Assessment (HOMA), Quantitative Insulin Sensitivity Check Index (QUICKI), McAuley, and Fasting Insulin Resistance Index (FIRI) in type 2 DM patients. Also, fasting insulin (FI) levels were estimated in type 2 diabetics. Further, the correlation of FI with other surrogate markers of IR in type 2 DM was done.Settings and Design A hundred newly diagnosed patients with type 2 DM from Malwa population, Punjab, were considered for evaluation. Another 100 healthy individuals (age and sex-matched) were examined as controls.Methods and Material Fasting blood glucose, FI, and lipid profile were estimated, and IR was calculated using McAuley index (McA), HOMA, QUICKI, and FIRI.Statistical Analysis Used The statistical analysis was performed on the above-mentioned clinical interpretations. The Cohen’s kappa test was used to affirm the agreement.Results FI levels in patients with type 2 diabetes were significantly higher (20.8 ± 9.05 µIU/L) than controls (7.93 ± 1.01 µIU/L). IR by surrogate markers was found significant in the study group. The 76% patients with type 2 diabetes ended up as resistant to insulin by FI measurement, almost equivalent to McA, 80%; HOMA, 88%; FIRI, 88%; and QUICKI, 90%. A notable correlation was highlighted between FI and McA manifesting IR (p < 0.01, r = −0.85). We calculated the statistical correlation of FI with HOMA, QUICKI, and FIRI indices (p < 0.01, r = 0.93; p < 0.01 r = −0.92; and p < 0.01, r = +0.93, respectively). The agreement visible from Cohen’s kappa test also affirms the same (k = 0.9 for McA).Conclusion We concluded that all the surrogate markers for IR were specific when compared with FI, but in terms of sensitivity McA was found to be more sensitive as it includes markers of dyslipidemia, which is the precipitating factor of metabolic derangements so as the IR in type 2 DM.
Keywords: serum insulin; FIRI; HOMA index; insulin resistance; McAuley index; QUICKI; type 2 diabetes mellitus